2001
DOI: 10.1046/j.1365-2893.2001.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of thymosin‐α1 and interferon‐α on Th1 and Th2 cytokine synthesis in patients with chronic hepatitis C

Abstract: Current evidence suggests that increased expression of Th1-associated cytokines is important for immune-mediated eradication of hepatitis C infection, while an increase in Th2-associated cytokines is associated with persistence of infection. In this study we evaluated the effects of thymosin-alpha1 (TA1), a naturally occurring thymic peptide, and interferon-alpha (IFN-alpha) on cytokine production in peripheral blood mononuclear cells from untreated patients with chronic hepatitis C. We examined the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Incubation of Ta1 in combination with IFNa was able to reverse the IFN-induced increase of IL-10. Finally, we confirmed that Ta1 amplifies the synthesis of IFN-induced antiviral protein 2,5-OAS [17].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Incubation of Ta1 in combination with IFNa was able to reverse the IFN-induced increase of IL-10. Finally, we confirmed that Ta1 amplifies the synthesis of IFN-induced antiviral protein 2,5-OAS [17].…”
Section: Discussionsupporting
confidence: 71%
“…The cells were resuspended at the concentration of 1 · 10 6 PBMC/mL and were then subjected to four different experimental conditions, all in the presence of Concanvalin A (ConA) at 10 mg/mL (Sigma); as previously reported [17,18], ConA was used as a polyclonal stimulus for triggering cytokine production.…”
Section: Methodsmentioning
confidence: 99%
“…TP was also efficient in vivo in mice with experimental gut-derived sepsis. The significantly reduced mortality of the animals was followed by reduced production of IL-4 and increased production of IL-2 [17] .Similarly, thymosin 1 treatment induced a significant increase in production of IL-2 and a decrease in production of IL-4 and IL-10 by T cells from patients with chronic hepatitis C [31] . Our results showed that higher concentrations of Thymsol inhibited proliferation of spleen T cells in a dose dependent manner.…”
Section: Placebo Differences ----------------------------------------mentioning
confidence: 87%
“…It was used widely in clinical treatment of hepatitis B, hepatitis C, HIV and some tumors, such as melanoma, lung cancer, leukemia, squamous epithelial cancer, colon cancer, etc. (Kullavanuaya et al, 2001;Andreone et al, 2001;Garaci et al, 2000Saruc et al, 2003. There are two kinds of thymus products for clinical practice: One is Zadaxin.…”
Section: Discussionmentioning
confidence: 99%